Preparation of teachers for training in research in the Library and Information Science School of the University of Costa Rica - Córdoba González, Saray (2011)
This article belongs to partial results obtained in a study that is performed by Escuela de Bibliotecología de la Universidad de Costa Rica. In this part it's intended to show the prevailing situation regarding the formation in investigation that the students receive, based on the analysis of the class programs and the current study plans, in graduate and post-graduate degree. For that, were analyzed the classes' programs from the curses: documental investigation techniques, assisted investigation, investigative methodology and investigation methods, bibliometry and infometry, so as the professional training that the teachers have and their opinions and thoughts left in interviews that were later discussed in a focal group. The investigation was done in the years of 2007 and 2008; the teachers that were chosen ( 10 in total) gave the classes specified above in the five years earlier from that period (2002-2006). Complementary, it was analyzed the relation between teachers and the organs linked to the organizational instances in charge of the investigation and finally they were add a series of content and style conclusions corresponding to the aspects pointed out before.